ISOLASI DAN AKTIVITAS ANTI MIKROBA BAKTERI ASAM LAKTAT DARI FERMENTASI NIRA KELAPA SAWIT - Fachrial, Edy; Harmileni, Harmileni (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2018)
The aim of the study was to isolate lactic acid bacteria (LAB) from palm oil sap and to investigate the anti microbial activity of LAB against pathogen bacteria, Staphylococcus aureus and Escherichia coli using disc diffusion method. Palm oil sap were enriched using spesific medium MRS (Man Rogosa Sharpe) broth overnight, serial dilution were conducted and the culture were spread on the surface of MRS agar and then incubated for 48 hours. The result showed the total colonies of LAB were 1,4 x 107 CFU/mL. 6 colonies were randomly selected namely EHN1, EHN2, EHN3, EHN4, EHN5 and EHN6. The selected colonies are classified as Gram positive and bacilli in morphology. Antimicrobial activity against pathogenic bacteria was investigated using disc diffusion method. Antimicrobial activity of isolates against E.coli and S.aureus were 12,2 mm; 9mm; 11mm; 11mm; 10,5mm; 12 mm dan 13,5mm; 11mm; 12mm; 11,5mm; 12mm; 12,5mm respectively. from these result it can be concluded that LAB isolated from oil palm sap has potential as probiotic.